Does ESG Impact Financial Performance? Financial Constraints And Financial Slack As Moderators - Richa Izzatul Zulfa; Ponny Harsanti (UNIVERSITAS PAKUAN, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) factors on financial performance, with financial constraints and financial slack serving as moderating variables. The study population consists of all energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. The sample was determined using purposive sampling, resulting in 7 companies with a total of 35 observations. Data analysis was conducted using Moderated Regression Analysis (MRA) with EViews software version 13. The results indicate that ESG has a positive effect on financial performance with a coefficient of 6.670 and a significance level of 0.034, financial constraints do not moderate the relationship between ESG and financial performance, as evidenced by a coefficient of -0.068 with a probability of 0.964. Conversely, financial slack was found to strengthen the effect of ESG on financial performance, with a coefficient of 3.029 and a significance level of 0.001. This study contributes to the development of ESG literature by incorporating financial condition as a moderating factor and provides practical implications for management in optimizing resources to support ESG implementation.